Numerical Mechanistic Modelling of Drug Release from Solvent-Removal Zein-Based In Situ Gel - Setthapong Senarat; Pornsarp Pornsawad; Nutdanai Lertsuphotvanit; Jesper Østergaard; Thawatchai Phaechamud (MDPI AG, 2023)
The development of effective drug delivery systems remains a focus of extensive research to enhance therapeutic outcomes. Among these, in situ forming gels (ISG) have emerged as a promising avenue for controlled drug release. This research focuses on the mathematical modeling of levofloxacin HCl (Lv) release from zein-based ISG using the cup method, aiming to mimic the environment of a periodontal pocket. The drug release behavior of the ISGs was investigated through experimental observations and numerical simulations employing forward and central difference formula. Notably, the experimental data for drug release from the 20% w/w zein-based ISG formulations closely aligned with the simulations obtained from numerical mechanistic modeling. In summary, 20% w/w zein-based ISG formulations demonstrated nearly complete drug release with the maximum drug concentration at the edge of the matrix phase values consistently around 100-105%, while 25% w/w zein-based ISG formulations exhibited somewhat lower drug release extents, with values ranging from 70-90%. Additionally, the rate of drug transport from the polymer matrix to the external phase influenced initial release rates, resulting in a slower release. The utilization of glycerol formal as a solvent extended drug release further than dimethyl sulfoxide, thanks to denser matrices formed by high-loading polymers that acted as robust barriers to solvent removal and drug diffusion. Furthermore, UV-vis imaging was utilized to visualize the matrix formation process and solvent diffusion within the ISGs. The imaging results offered valuable insights into the matrix formation kinetics, controlled drug release mechanisms, and the influence of solvent properties on drug diffusion. The combination of mathematical modeling and experimental visualization provides a comprehensive understanding of drug release from zein-based ISGs and offers a foundation for tailored drug delivery strategies.